Metallurgical coatings and thin films, 1991 : proceedings of the 18th International Conference on Metallurgical Coatings and Thin Films, San Diego, CA, U.S.A., April 22-26, 1991. - McGuire, G. E.; McIntyre, D. C. (Dale C.); Hofmann, S. (Siegfried) (Elsevier ; Sole distributor in the USA and Canada, Elsevier Science Pub. Co., 1991)
The contributions in this two-volume set represent the work of over two hundred international researchers from universities, government laboratories and industry, with diverse backgrounds and interests in a wide range of coatings and thin film processes. The two hundred and six papers attest to the fact that Metallurgical Coatings is a rapidly growing field attracting experts from the large materials, scientific and technical community. The papers will be a useful and dynamic tool for those wishing to increase their knowledge on metallurgical coatings, as well as providing a guide to recent literature in this field.